Pertumbuhan dan Hasil Jagung Hibrida pada Ultisol - Putra, Irawan Haji; Suprapto, Suprapto; Ganefianti, Dwi Wahyuni (Badan Penerbitan Fakultas Pertanian (BPFP), Fakultas Pertanian, Universitas Bengkkulu, 2015)
Hybrid corn cultivated on Ultisol performs high production when organic matter and liming are incorporated into the soil under high application of fertilizer. This agricultural practice resulted in high cost production. A series of researches with the goal to produce high yielding of hybrid corn under low input of fertilizer is going to be a benefit. Field experiment was conducted from April until July 2010 in Manna, South Bengkulu. Single factor consisted of 7 genotipes of corn was set using Randomized Complete Block Design. The seven genotypes were marked as H1, H2, H3, H4, H5, H6 (Prima), and H7 (DK); the last two of which were commercial varieties commonly grown by farmers. The genotypes that showed good adaptation on Ultisol were H1, H2, and H3. These genotypes yielded 5.11 tons ha-1 for H1, 5.56 tons ha-1 for H2, and 5.64 tons ha-1 which were higher than commercial varieties (4.46 tons ha-1 for Prima and 4.62 tons ha-1 for DK). Plant height for H1, H2, and H3 were 1.78 m, 1.80 m, and 1.88 m respectively, while plat height of Prima and DK were 1.45 m and 1.51 m.